Surgical Management of a Large Periradicular Lesion in Mandibular Anterior Teeth associated with Trauma - Garg, Ridhi; Singhal, Ankit (Journal of Orofacial Research, 2013)
consequence of dental traumatic injuries. Early management of such cases is mandatory in order to prevent subsequent pathological changes that could further complicate the treatment. Pulp necrosis, chronic and cystic apical periodontitis can be the fate if these teeth are left untreated. Despite these serious complications, root canal treatment followed by apical surgery is considered a valid treatment option when such cases become complicated with large periapical lesions. This case report discusses the orthograde endodontic management, the surgical approach and the clinical outcomes of longstanding traumatic teeth with large cystlike periradicular lesion.